The principle of independence of judges as a norm of regional customary international law in Europe - Fomina, Gabriela (Riga Graduate School of Law, 2020)
In the face of repeated attacks on the independence of the judiciary and its members by several European governments in the last preceding years, the status of the observance to the principle of independence of judges in Europe has become a subject to a discussion. In the attempts to address the issue, the present thesis sets the determination of whether the said principle constitutes a norm of regional customary international law in Europe as its purpose. To that end, the theoretical concept of independence of judges is first examined and an ad hoc definition of its main elements is constructed. Consequently, based on an established methodology of identification of norms of customary international law and the ad hoc definition, practice of six representative European states of ensuring guarantees of independence of judges in their national legislation is examined, which is finally analysed together with the case law of the European courts
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Judges